Rapid Analyses of Proteomes and Interactomes Using an Integrated Solid-Phase Extraction-Liquid Chromatography-MS/MS System. - Binai, N; Marino, F; Soendergaard, P; Bache, N; Mohammed, S; Heck, A (2014)
Here, we explore applications of a LC system using disposable solid-phase extraction (SPE) cartridges and very short LC-MS/MS gradients that allows for rapid analyses in less than 10 min analysis time. The setup consists of an autosampler harboring two sets of 96 STAGE tips that function as precolumns and a short RP analytical column running 6.5 min gradients. This system combines efficiently with several proteomics workflows such as offline prefractionation methods, including 1D gel electrophoresis and strong-cation exchange chromatography. It also enables the analysis of interactomes obtained by affinity purification with an analysis time of approximately 1 h. In a typical shotgun proteomics experiment involving 36 SCX fractions of an AspN digested cell lysate, we detected over 3600 protein groups with an analysis time of less than 5.5 h. This innovative fast LC system reduces proteome analysis time while maintaining sufficient proteomic detail. This has particular relevance for the use of proteomics within a clinical environment, where large sample numbers and fast turnover times are essential.